Recent progress in inorganic and composite coatings with bactericidal capability for orthopaedic applications - Simchi, Abdolreza; Tamjid, E.; Pishbin, F.; Boccaccini, Aldo R. (Nanomedicine, 2011)
This review covers the most recent developments of inorganic and organic-inorganic composite coatings for orthopedic implants, providing the interface with living tissue and with potential for drug delivery to combat infections. Conventional systemic delivery of drugs is an inefficient procedure that may cause toxicity and may require a patient's hospitalization for monitoring. Local delivery of antibiotics and other bioactive molecules maximizes their effect where they are required, reduces potential systemic toxicity and increases timeliness and cost efficiency. In addition, local delivery has broad applications in combating infection-related diseases. Polymeric coatings may present some disadvantages. These disadvantages include limited chemical stability, local inflammatory reactions, uncontrolled drug-release kinetics, late thrombosis and restenosis. As a result, embedding of bioactive compounds and biomolecules within inorganic coatings (bioceramics, bioactive glasses) is attracting significant attention. Recently nanoceramics have attracted interest because surface nanostructuring allows for improved cellular adhesion, enhances osteoblast proliferation and differentiation, and increases biomineralization. Organic-inorganic composite coatings, which combine biopolymers and bioactive ceramics that mimick bone structure to induce biomineralization, with the addition of biomolecules, represent alternative systems and ideal materials for "smart" implants. In this review, emphasis is placed on materials and processing techniques developed to advance the therapeutic use of biomolecules-eluting coatings, based on nanostructured ceramics. One part of this report is dedicated to inorganic and composite coatings with antibacterial functionality. From the Clinical Editor: Inorganic and composite nanotechnology-based coating methods have recently been developed for orthopedic applications, with the main goal to provide bactericide and other enhanced properties, which may result in reduced need for pharmaceutical interventions and overall more cost effective orthopedic procedures. This review discusses key aspects of the above developments. © 2011 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.recent
Keywords: Antimicrobial; Ceramics; Coatings; Composites; Drug-eluting implants; Nanostructures